The Age-Driven Decline in Neutrophil Function Contributes to the Reduced Efficacy of the Pneumococcal Conjugate Vaccine in Old Hosts - Simmons, Shaunna R.; Tchalla, Essi Y. I.; Bhalla, Manmeet; Bou Ghanem, Elsa N. (Frontiers in Cellular and Infection Microbiology, 2022)
Despite the availability of vaccines, Streptococcus pneumoniae (pneumococcus) remain a serious cause of infections in the elderly. The efficacy of anti-pneumococcal vaccines declines with age. While age-driven changes in antibody responses are well defined, less is known about the role of innate immune cells such as polymorphonuclear leukocytes (PMNs) in the reduced vaccine protection seen in aging. Here we explored the role of PMNs in protection against S. pneumoniae in vaccinated hosts. We found that depletion of PMNs in pneumococcal conjugate vaccine (PCV) treated young mice prior to pulmonary challenge with S. pneumoniae resulted in dramatic loss of host protection against infection. Immunization boosted the ability of PMNs to kill S. pneumoniae and this was dependent on bacterial opsonization by antibodies. Bacterial opsonization with immune sera increased several PMN anti-microbial activities including bacterial uptake, degranulation and ROS production. As expected, PCV failed to protect old mice against S. pneumoniae. In probing the role of PMNs in this impaired protection, we found that aging was accompanied by an intrinsic decline in PMN function. PMNs from old mice failed to effectively kill S. pneumoniae even when the bacteria were opsonized with immune sera from young controls. In exploring mechanisms, we found that PMNs from old mice produced less of the antimicrobial peptide CRAMP and failed to efficiently kill engulfed pneumococci. Importantly, adoptive transfer of PMNs from young mice reversed the susceptibility of vaccinated old mice to pneumococcal infection. Overall, this study demonstrates that the age-driven decline in PMN function impairs vaccine-mediated protection against Streptococcus pneumoniae.